2010
DOI: 10.1684/agr.2009.0371
|View full text |Cite
|
Sign up to set email alerts
|

L’équitable, le bio et le goût. Quels sont les effets de la double labellisation bio-équitable sur le consentement à payer de consommateurs ?

Abstract: L'é quitable, le bio et le goû t. Quels sont les effets de la double labellisation bio-é quitable sur le consentement à payer de consommateurs ? Ré suméDans cet article, nous mesurons à partir d'une expérimentation de type BDM (Becker-DeGroot-Marschak), l'effet d'une double labellisation « Agriculture biologique et commerce équitable » sur le prix que les consommateurs sont prêts à payer pour du chocolat. Nous montrons que, globalement, la double labellisation ajoute de la valeur aux produits mais que le goût … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 6 publications
3
6
0
10
Order By: Relevance
“…In other words, the overall value of a combination of labels is not the mere aggregate of the values assigned to each of the labels in the combination. This finding reinforces that of Tagbata and Sirieix (2010), among others. Table 2 allows us to further extend the analysis of this effect by showing differences according to label combination.…”
Section: Discussion Of Hypothesis 2: Embedding Effect and Prototypicasupporting
confidence: 92%
See 2 more Smart Citations
“…In other words, the overall value of a combination of labels is not the mere aggregate of the values assigned to each of the labels in the combination. This finding reinforces that of Tagbata and Sirieix (2010), among others. Table 2 allows us to further extend the analysis of this effect by showing differences according to label combination.…”
Section: Discussion Of Hypothesis 2: Embedding Effect and Prototypicasupporting
confidence: 92%
“…This study did not, however, conclude that the increased value for dual labelling was greater than the sum of that for each label individually. These findings were partially supported by Tagbata and Sirieix (2010). In an experiment conducted on 102 consumers (BDM lottery), the authors showed that the dual labelling of a bar of chocolate ('organic' and 'fair trade') increased the value of the chocolate for the consumers, but resulted in a lower willingness to pay than the sum of the WTP for each of the labels individually.…”
Section: Main Authorsmentioning
confidence: 87%
See 1 more Smart Citation
“…4.). En se référant à d'autres chercheurs, ils affirment que « la présence de plusieurs labels peut accroitre l'incertitude et révéler des influences diverses sur les comportements des consommateurs » (Tagbata et Sirieix, 2010 ;Janssen et Hamm, 2012 ;Dekhili et Achabou, 2013). Ces observations nous ont incités à faire une analyse plus détaillée sur l'expression de l'identité de la marque à travers son discours et sur l'expression du degré de son engagement dans le discours qui représente le produit.…”
Section: Introductionunclassified
“…Les produits issus du commerce équitable connaissent-ils le même décalage ? C'est ce qu'explorent Tagbata et Sirieix (2010) à propos du chocolat équitable. Ils montrent que, même si les préoccupations éthiques des individus sont importantes, la qualité gustative reste un critère de choix dominant.…”
unclassified